1978
DOI: 10.1159/000162906
|View full text |Cite
|
Sign up to set email alerts
|

Increased Trypsin Sensitivity of Cell Surface Macromolecules after Malignant Transformation

Abstract: The effect of treatment with 0.04% (w/v) trypsin (EC 3.4.4.4) for 3 h on the electrophoretic mobility (EPM) of polyoma-virus malignantly transformed BHK21 cells (Py6) and their normal counterparts has been investigated. These particular conditions were chosen because an earlier study had shown that such treatment released material from the Py6 cells which was not obtained from the BHK21 cells. The negative EPM of the Py6 cells at pH 7.5 was greatly increased by this treatment; whereas the EPM of the BHK21 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Recently, using the BHK21 and polyoma virus-transformed cell system, Latner and Turner (1978) have shown that such extra basic material also occurs in the transformed cells. Similar increases in basic material have also been reported on lymph node cells derived from acute lymphoblastic leukaemia (Cook and Jacobson, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the BHK21 and polyoma virus-transformed cell system, Latner and Turner (1978) have shown that such extra basic material also occurs in the transformed cells. Similar increases in basic material have also been reported on lymph node cells derived from acute lymphoblastic leukaemia (Cook and Jacobson, 1968).…”
Section: Discussionmentioning
confidence: 99%